2022
DOI: 10.1002/vnl.21909
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of melamine borate coated red phosphorus microcapsules and use of zinc borate as synergistic flame retardant in polyethylene

Abstract: Microcapsules (Mic-MBP) based on the melamine borate coated red phosphorus (RP) were prepared, and its synergistic flame retardant with zinc borate (ZB) on polyethylene (PE) was investigated. The flame retardant properties of the PE/20% Mic-MBP/10%ZB were superior to that of PE/20%RP/10%ZB. Furthermore, the limiting oxygen index of PE/20%Mic-MBP/10%ZB was 25.2%, and PE/20%Mic-MBP/10%ZB reached the UL-94V-0 rating. Compared with PE, the peak heat release rate (pk-HRR), total heat release (THR) and average effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The RP acted as acid source, and the shell materials acted as gas and carbon sources. During combustion, Mic−DP first decomposed to nonflammable inert gases, including NH 3 and H 2 O [ 23 ], resulting in the reduction of concentration of flammable volatiles. Then, RP formed phosphorous acid and phosphorous free radicals, which reacted with crossed β−CD to promote the formation of carbon layer and trapped the active free radicals in the gas phase, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RP acted as acid source, and the shell materials acted as gas and carbon sources. During combustion, Mic−DP first decomposed to nonflammable inert gases, including NH 3 and H 2 O [ 23 ], resulting in the reduction of concentration of flammable volatiles. Then, RP formed phosphorous acid and phosphorous free radicals, which reacted with crossed β−CD to promote the formation of carbon layer and trapped the active free radicals in the gas phase, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine and acetone were purchased from Guangzhou Chemical Reagent Factory, Guangzhou, China. Microcapsules based on melamine borate coated red phosphorus (Mic−MBP) were prepared by our laboratory [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is not unexpected as MRP and other phosphorus-containing FRs are known to be able to generate POÁ free radicals in case of oxidation, which captures HÁ and ÁOH free radicals and terminates chain reaction in flame. [5,[34][35][36][37] Insufficient combustion in the gas phase leads to increase of smoke release.…”
Section: Acid Erosion Characterizationmentioning
confidence: 99%
“…30,31 However, RP has some drawbacks such as strong moisture absorption and chemical instability, leading to the requirement to combine it with other flame retardants. It has been found that RP exhibits a flame-retardant synergistic effect with novolac and melamine, 32 aluminum isobutylphosphinate, 33 melamine borate and zinc borate, 34 and titanium dioxide. 35 In this work, RP and MH were introduced into PP/EG composites to enhance the compactness of the char structure due to the covering and adhesive efficiency of high-viscosity compounds generated by the thermal decomposition and interaction of these materials.…”
Section: Introductionmentioning
confidence: 99%